Urgency of Parents as Smart Parenting Against Child Education in The Industrial Revolution Era 4.0 - Rumiati Rumiati; Siska Fitri Purbayani; Tri Irmawati; Ratna Hidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
The purpose of writing this article is to examine the urgency of parents to become smart parenting in educating children in the industrial revolution era 4.0. In the era of the industrial revolution 4.0 the challenges faced by parents in educating their children are increasingly severe. The characteristics of children in this era have different characteristics from previous generations. The difference in characteristics requires parents to provide appropriate parenting strategies in improving the quality of children's education. Smart parenting is a parenting strategy that has a smart way to educate their children in order to achieve optimal development and can solve problems in their child's development. Smart parenting is suitable to be used in educating children in the industrial revolution era 4.0 because it can improve the ability of parents in terms of educating children so that they can optimally support children's development.